2014
DOI: 10.1111/1755-0998.12279
|View full text |Cite
|
Sign up to set email alerts
|

DNA barcoding of Murinae (Rodentia: Muridae) and Arvicolinae (Rodentia: Cricetidae) distributed in China

Abstract: Identification of rodents is very difficult mainly due to high similarities in morphology and controversial taxonomy. In this study, mitochondrial cytochrome oxidase subunit I (COI) was used as DNA barcode to identify the Murinae and Arvicolinae species distributed in China and to facilitate the systematics studies of Rodentia. In total, 242 sequences (31 species, 11 genera) from Murinae and 130 sequences (23 species, 6 genera) from Arvicolinae were investigated, of which 90 individuals were novel. Genetic dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 62 publications
0
15
0
Order By: Relevance
“…For example, Rattus (under BIN BOLD:AAB2208) detected from blowfly-derived DNA, cage traps, and scat collection likely represents Rattus "sp. R3" (Pages et al 2010), a classic "dark taxon" (see Wilson et al 2014) whereby it has not yet been formally described and is likely to be reported as R. andamanensis, R. argentiventer, or R. tanezumi in studies relying on visual diagnosis (Robins et al 2007;Pages et al 2010;Latinne et al 2013;Li et al 2015). The BIN associated with this taxon comprises DNA barcode members under the traditional names Rattus tanezumi, Rattus tiomanicus, Rattus rattus, Rattus sp., and Rattus sp.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Rattus (under BIN BOLD:AAB2208) detected from blowfly-derived DNA, cage traps, and scat collection likely represents Rattus "sp. R3" (Pages et al 2010), a classic "dark taxon" (see Wilson et al 2014) whereby it has not yet been formally described and is likely to be reported as R. andamanensis, R. argentiventer, or R. tanezumi in studies relying on visual diagnosis (Robins et al 2007;Pages et al 2010;Latinne et al 2013;Li et al 2015). The BIN associated with this taxon comprises DNA barcode members under the traditional names Rattus tanezumi, Rattus tiomanicus, Rattus rattus, Rattus sp., and Rattus sp.…”
Section: Discussionmentioning
confidence: 99%
“…We appended the new data generated in the present study to those used in our previous study and data from GenBank364041424388 and reconstructed a phylogenetic tree using CytB and the concatenated sequences of the four DNA fragments. The sequences were aligned with ClustalW89 as implemented in MEGA90.…”
Section: Methodsmentioning
confidence: 99%
“…example, a success rate close to 100% were reported for Germany herpetofauna 48 (Hawlitschek et al 2016), more than 90% for Chinese rodents (Li et al 2015a), more 49 than 80% for freshwater fishes of the Congo basin ; Decru et al…”
mentioning
confidence: 95%